Effect of Eco-Enzyme’s Storage Duration on Hydrogen Peroxide Level and Its Antibacterial Activity - Primarista, Ni Putu; Imam Abu Hanifah; Arie Srihadyastutie; Sasangka Prasetyawan; Ulfa Andayani; Tri Adyati (Graduate School, Universitas Brawijaya, 2023)
Eco-enzyme is a filtrate produced by fermenting sugar and a mixture of organic matter for 3 months. Eco-enzymes have been widely used as cleaning fluids and disinfectants. This study aims to investigate the levels of hydrogen peroxide and the antibacterial activity of eco-enzymes stored at different times. Hydrogen peroxide level was analyzed by redox titration and the antibacterial activity against Escherichia coli and Staphylococcus aureus was analyzed by paper disc method. This study shows that there were significant differences in the levels of hydrogen peroxide and the antibacterial activity of the eco-enzymes stored for a certain time. Hydrogen peroxide levels increased from 0 months of storage to reach the highest point at 10 months of storage with 2664.9 ppm and then it began to decrease to the lowest point at 114 months of storage. The highest antibacterial activity against Escherichia coli and Staphylococcus aureus was shown by eco-enzyme stored for 0 months, with inhibitory zones of 6.37 mm and 6.59 mm, respectively. Eco-enzyme no longer showed antibacterial activity after 15 months of storage. Overall, the storage duration of the eco-enzyme affects the hydrogen peroxide level and antibacterial activity against Escherichia coli and Staphylococcus aureus due to the amount of lactic acid bacteria in the eco-enzyme. Keywords: antibacterial activity, eco enzyme, hydrogen peroxide, storage duration